Mycorrhyzal fungi of Vanilla: root colonization patterns and fungal infection - Porras Alfaro, Andrea; Bayman, Paul (Lankesteriana: International Journal on Orchidology, 2016)
Orchid mycorrhizal fungi are characterized by the presence of complex, globose masses of hyphe, called pelotons, in the cortex of the root (Hadley et al. 1989, Esnault et al. 1994). Extent and patterns of infections are very variable, and this variation is observed in many epiphytic orchids and some terrestrial tropical orchids (Hadley et al. 1989, Allen 1991).